Early degradation of silicon heterojunction PV modules installed on horizontal single-axis trackers in desert climate - A.A. Abdallah (22150156) (2025)
We present our latest findings on the early degradation of photovoltaic (PV) silicon heterojunction (HJT) modules installed in harsh desert climates for about two and half years. The results are compared with the benchmark modules with monofacial and bifacial passivated emitter rear contact (PERC) and passivated emitter rear totally diffused (PERT) technologies installed on a horizontal single-axis tracker (HSAT). These findings showed an early degradation of 62 % of the inspected PV modules induced by their field exposure to a desert climate. Ultraviolet fluorescence (UVF) imaging showed signatures of early degradation of encapsulant materials, while near-infrared absorption spectroscopy (NIRA) identified PV module materials in the field. We found evidence of the use of different encapsulant materials and different variants of the same encapsulant materials by the module manufacturer. In contrast to the PERC PV modules with thermoplastic polyolefin (TPO) and polyolefin elastomer (POE) encapsulants, HJT modules with TPO encapsulants showed distinct UVF patterns indicating early degradation. Similarly, all the HJT PV modules with POE and ethylene vinyl acetate (EVA) encapsulant showed UVF degradation patterns. The PERC-2 PV modules exhibited UVF degradation patterns as well but with no significant change in the maximum power Pmax. While the Pmax of the HJT-1, HJT-2a, and HJT-2b dropped by −5.9 %, −3.0 %, and −7.3 %, respectively. The study showed that harsh desert climate induces early encapsulant aging, particularly, glass-glass modules showing the importance of encapsulant material selection. Other Information Published in: Solar Energy Materials and Solar Cells License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.solmat.2025.113899